ISOLASI, PREVALENSI DAN UJI SENSITIVITAS ANTIBIOTIK TERHADAP Escherichia coli SEROTIPE O157 PADA AYAM BURAS YANG DIPERDAGANGKAN DI PASAR TRADISIONAL DI KOTA KUPANG - Nathasya Pelt; Maxs U.E. Sanam; Elisabet Tangkonda (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2016)
Escherichia coli is a Gram negative bacteria of cocobacill in ranging from 2,2 μm and 0,4-0,7μm and 0,8 μm diameter , occurring single or in pairs, flagella pertiricus motile, facultative anaerobic, and including to eneterobactericeae family. E. coli inhabits the lower ileum and large intestine of most vertebrates with colonization of the neonatal gastrointestinal tract occurring within hours of birth. E. coli O157:H7 is a zoonotic agent, can causes bloody diarrhea, hemolitycuremic syndrome (HUS) and trombotyc thrombocythopenic purpura (TTP) in human. Chicken was known as one important reservoir of E. coli O157:H7. The aims of this study were to isolate, prevalence and antibiotic sensitivity test of E. coli O157:H7 in local chickens are selling in the traditional market Kupang City. The bacteria was isolated by culturing the agent in Eosin Methylene Blue Agar (EMBA) medium, isolated from emba then used to Gram staining, Biochemical test, O157 Latex agglutination test and antibiotic sensitivity test. Results of study showed that 33 (41,25%) out of 80 chicken’s fecal samples were identified as E. coli O157. This E. coli O157 are sensitive to ciprofloxacin, ampicilin, amoxicillin, tetracycline and cefoxitin. ciprofloxacin in the Muller Hinton Agar media (MHA). The results showed that P. multocida was isolated from one tracheal swab samples. This P. multocida isolates were sensitive to ciprofloxacin, while are resistant to ampicillin, amoxicillin, tetracycline and cefoxitin.